Optimizing Immigration Services Through Capacity Building: An Analysis of Implementation and Its Impact on Public Service Performance in Indonesia (Case Study: Class II Non-TPI Immigration Office in Blitar, 2025): Penelitian - Indras Riana Nur Lukman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study examines capacity building aimed at enhancing immigration service performance at the Class II Non-TPI Blitar Immigration Office, an entity playing a strategic role in national security, tourism, and population mobility. Challenges such as a shortage of skilled personnel, suboptimal information technology infrastructure, and a lack of inter-agency coordination were addressed through continuous training, the digitalization of information systems, and institutional reform. Employing a qualitative case study approach—utilizing interviews, observations, and document analysis—the research demonstrates that capacity building improves service efficiency, transparency, and accuracy. Human resource training and digitalization accelerated document verification and minimized administrative errors, while institutional restructuring optimized workflows. However, service congestion during peak hours and resistance among some staff members toward the new systems remain obstacles. The synergy of competency enhancement, digital transformation, and structural reform proved effective in optimizing immigration services. The study recommends strengthening digital infrastructure and implementing change management strategies to mitigate resistance and foster accountable governance.